Expression and Functional Roles of Eukaryotic Initiation Factor 4A Family Proteins in Human Cancers - Xue, Chen; Gu, Xinyu; Li, Ganglei; Bao, Zhengyi; Li, Lanjuan (Frontiers in Cell and Developmental Biology, 2021)
The dysregulation of mRNA translation is common in malignancies and may lead to tumorigenesis and progression. Eukaryotic initiation factor 4A (eIF4A) proteins are essential for translation, exhibit bidirectional RNA helicase function, and act as RNA-dependent ATPases. In this review, we explored the predicted structures of the three eIF4A isoforms (eIF4A1, eIF4A2, and eIF4A3), and discussed possible explanations for which function during different translation stages (initiation, mRNA localization, export, and mRNA splicing). These proteins also frequently served as targets of microRNAs (miRNAs) or long noncoding RNAs (lncRNAs) to mediate epithelial-mesenchymal transition (EMT), which was associated with tumor cell invasion and metastasis. To define the differential expression of eIF4A family members, we applied the TIMER website. We figured out that the eIF4A family genes were differently expressed in specific cancer types. We also found that the level of the eIF4A family genes were associated with abundant immune cells infiltration and tumor purity.. The associations between eIF4A proteins and cancer patient clinicopathological features suggested that eIF4A proteins might serve as biomarkers for early tumor diagnosis, histological classification, and clinical grading/staging, providing new tools for precise and individualized cancer treatment.